INNOVATIVE BRANDING SUPPORT FOR ORGANIC-FERTILIZER MSME: EXPLORING KARANGWARU SRAGEN'S LOCAL POTENTIAL: DUKUNGAN BRANDING INOVATIF UNTUK UMKM PUPUK ORGANIK: MENJELAJAHI POTENSI LOKAL KARANGWARU SRAGEN - Putri, Ika Swasti; Wijaya, Nur Rizki; Widiastutik, Rika Nur; Wiguna, Ratu Aghnia Raffaidy (Faculty of Vocational Studies, Universitas Airlangga, 2025)
Background: Organic-fertilizer MSMEs in Karangwaru, Sragen, have clear growth prospects but remain competitively fragile due to weak branding, rudimentary packaging, and limited use of digital channels. Unlike the well-studied output side (FMCG/post-harvest), input-side branding for farm supplies is under-addressed, thus constraining market access. Objective: This community service program aims to build branding capability through coherent visual identity systems, market-ready packaging with compliant labels, trademark preparation, and actionable digital marketing routines. Method: A participatory design anchored in baseline diagnostics, intensive workshops, and three months of mentored implementation. Activities blended experiential learning (logo/packaging co-creation and supplier briefs), practice with social media and e-commerce, and clinic-style coaching to institutionalize internal branding routines. Results: Capability and performance improved. Leads +75%; conversion 2%—3.5%; retention 60%—78%; brand awareness +40%. Triangulated qualitative evidence (owners/retail partners, field notes, shelf audits) indicates better market positioning—stronger on-shelf salience, more buyer inquiries, and heightened perceived quality due to clearer, compliant information architecture. Conclusion: Emphasizing packaging and capability building yielded measurable market benefits for rural input-side MSMEs and laid a more stable foundation for sustained competitiveness.